PENGARUH KINERJA GURU TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMK NEGERI 2 BARRU - Riska Amaliah; Nurindah; Nasir (Jurnal Riset Guru Indonesia, 2023)
This study aims to determine the effect of teacher performance on the mathematics learning outcomes of students at SMK Negeri 2 Barru. The method that the writer uses is a descriptive correlation, which is a method to find the relationship between the performance of Mathematics teachers and student learning outcomes. The sample in this study were class XI students of SMK Negeri 2 Barru for the 2022/2023 academic year, totaling 102 students from 3 classes and 3 Mathematics teachers. Data collection techniques in this study were documentation and questionnaires. The data analysis technique used is descriptive statistical data analysis. The analysis used to determine the effect of teacher performance is measured by the Likert scale and the analysis of inferential statistical data to find the correlation coefficient using the rough number formula. The results showed that there was no significant correlation between teacher performance and mathematics learning outcomes for students at SMK Negeri 2 Barru. This can be seen from the results of the product-moment correlation analysis between the independent variable (X) and the related variable (Y) which is then interpreted with a table at a significant level of 5% and 1% so that it is clear that the value of count = 0.569 at table 5% with df = 1 is 0.996, and recount of 1% is 0.987 so it appears that teacher performance has no effect on the mathematics learning outcomes of students at SMK Negeri 2 Barru. Which states that H1 is rejected and H0 is accepted. The magnitude of the influence of the performance of Mathematics teachers on students of SMK Negeri 2 Barru is 0.569%, the results of these calculations are through a test of the determinant coefficient (KD) = r2 × 100 or 0.5692 × 100 = 0.32 while 32% is influenced by other factors. Based on the results of this study it can be concluded that there is no effect of teacher performance on the mathematics learning outcomes of students at SMK Negeri 2 Barru.